Human creativity and the instinctive circulation of money in the global economy - Toan, Vu; Quoc, Nguyen Anh (Edelweiss Applied Science and Technology, 2025)
The article's content aims to clarify the transformation between humans and money in terms of means and purposes, subjects, and products, which is both historically specific and a trend of social development. To achieve this purpose, the article's content approaches the methodology of humanistic and social philosophy while using qualitative methods to analyze and synthesize the transformation process between human and monetary life. The results achieved in the content of the article show that money is a creative product of humans that becomes a means of exchange; when money becomes popular, the state's monopoly function of issuing currency becomes a requirement of life. The power of money in social management and distribution makes the function of the state become a foreign currency business in maintaining the price of domestic currency in the commodity economy. The article's content draws the following conclusions: First, humans are the subjects that become the products of money. Second, the state exists in all possible forms, one of which is the monopoly of currency issuance. Third, commodity enterprises become foreign currency enterprises, making the monopoly of currency issuance a function of maintaining the price of domestic currency. Fourth, foreign currency trading becomes speculative in the key currency, causing this key currency to be continuously issued. Fifth, when the US dollar inflates, the price shock awakens humanity in the struggle for money, and a new and innovative form of currency emerges.